Media coverage of banking and financial news - Picard, RG; Selva, M; Bironzo, D (Reuters Institute for the Study of Journalism, 2014)
This report examines how media covered the banking and financial sector from 2007 to 2013. It is based on an analysis of banking media reports from 12 news outlets in four European countries, plus four English-language business news outlets with wide European circulation.